The economic development of the Rhine river basin in the Roman period (30 BC - AD 406) - Franconi, T (2014)
The economic development of frontier regions has been neglected in the study of the Roman economy. Traditional core/periphery models suggest that frontiers were marginal zones dependent on a wealthy Mediterranean core, and this view has dominated scholarship for more than thirty years. In light of recent work on the Roman economy, it is clear that many old models need to be reappraised; this thesis examines the economic development of frontiers through the case study of the Rhine River Basin. This region formed one of Rome’s northern frontiers for more than 400 years and has a rich tradition of detailed archaeological and historical research. Using data from the Rhine frontier, this thesis re-examines the nature of frontier economies, arguing that they were dynamic, versatile, and complex rather than subaltern and undeveloped. A new model, based in the analytic framework of economic geography, is suggested as a replacement in order to appreciate the realities and potential of frontier economies.